Choosing to pray for the past - Mawson, T (Nordic Society for Philosophy of Religion, 2024)
Most of those who believe in the theistic God offer petitionary prayers to Him, supposing that, whatever else they may be doing when they are doing so, they are increasing the chances that reality will conform to their prayerfully expressed desires for it. On several clusters of views that are popular with theists, praying that the past have been a certain way seems to make no less sense than praying that the future will be a certain way, for God is atemporal and thus for Him the time at which a prayer happens to be uttered relative to the outcome it concerns seems likely to be an irrelevance. In this paper, I outline one reason why it is not an irrelevance and draw out the implication for whether or not one can coherently consider oneself to be choosing to utter efficacious prayers for the past.